2010
DOI: 10.1111/j.1751-553x.2010.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and robustness of blood variables in an antidoping context

Abstract: In conclusion, our data clearly demonstrate that as long as the World Anti-Doping Agency's guidelines are followed rigorously, all blood results reach the quality level required in the antidoping context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Most recently, Robinson et al . reported a more comprehensive data set than their initial study but again concluded that reticulocytes were stable through 72 h at 4 °C when measured on a Sysmex XT‐2000i.…”
Section: Discussionmentioning
confidence: 96%
“…Most recently, Robinson et al . reported a more comprehensive data set than their initial study but again concluded that reticulocytes were stable through 72 h at 4 °C when measured on a Sysmex XT‐2000i.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, since the OFF-score, a parameter used to calculate the probability of blood doping in athletes, depends on Hb concentration and Ret count (Sottas et al, 2010; Robinson et al, 2011; which remained stable), WBC may reduce the result of this score and, thus, cannot be considered a performance enhancing practice. On the other hand, the use of WBC to mask illicit practices is unjustified because the potential decrease in Hb is too small and the change itself is short-lasting and/or temporary (Lombardi et al, 2013a).…”
Section: Hematologymentioning
confidence: 99%
“…[29,30] If such storage conditions have not been respected or are not documented, careful scrutiny of the red cell indices (e.g.…”
Section: Collectionmentioning
confidence: 99%